Production of plant-expressed virus-like particle vaccines against infectious bronchitis coronavirus and vaccine efficacy in chickens - Abolnik, Celia (University of Pretoria, 2023)
Thesis (PhD (Production Animal Studies))--University of Pretoria, 2022.